SIMAP KONTRAKTBØRS - SIMPEL, EFFEKTIV OG SIKKER HANDEL MED KONTRAKTER - Bøgetoft, P.; Damgaard, I.; Nielsen, K.; Christensen, D. (Tidsskrift for Landøkonomi, 2008)
SIMAP KONTRAKTBØRS - SIMPEL, EFFEKTIV OG SIKKER HANDEL MED KONTRAKTER